Case Report: Dual resistance to dasatinib/olverembatinib in accelerated-phase cml: identification of a novel SPECC1L-inserted e8a2 BCR::ABL1 transcript and ABL1 V379I mutation - Fu, Jingjing; Tang, Yangming; Ruan, Xueqin; Wang, Runfa; Chen, Tong; Jiang, Li; He, Yanli; Xu, Zhihong; Wang, Balian; Zhang, Haiqin; Zhou, Jing; Lan, Mei; et al. (Frontiers in Oncology, 2025)
In chronic myeloid leukemia (CML), less than 2% of cases express atypical or rare BCR::ABL1 transcripts. The e8a2 BCR::ABL1 fusion transcript, a rare variant, has been reported in only 20 cases to date, primarily in case reports or case series. The direct junction between BCR exon 8 and ABL1 exon 2 generates a premature stop codon at position 7 after the fusion, while the insertion of certain sequences can result in the formation of an in-frame e8a2 transcript. To date, the insertion of SPECC1L gene sequences into e8a2 BCR::ABL1 fusion transcripts has been reported in two CML cases, and the V379I mutation (in ABL1) has been identified in two additional CML cases. We describe a case of accelerated-phase CML involving three key molecular abnormalities: the insertion of a 154 bp SPECC1L exon 4 sequence into the e8a2 BCR::ABL1 fusion transcript, a concomitant ABL1 V379I mutation, and deletions near the t(9;22) breakpoint on derivative chromosome 9 (der(9)). The patient’s clinical manifestations, cytogenetic features, and molecular genetic characteristics were summarized and discussed. Despite sequential therapy with full-dose dasatinib for 10 months and the third-generation tyrosine-kinase inhibitor (TKI) olverembatinib for 7 months, the patient experienced progressive disease. She ultimately achieved Major Molecular Response (MMR) after haploidentical hematopoietic stem-cell transplantation (haplo-HSCT). This case highlights the importance of comprehensive molecular profiling at diagnosis and the need to develop alternative therapeutic strategies for rare BCR::ABL1 variants.